FENOMENA ROB DI KOTA SEMARANG - Pratikso, Pratikso; Soedarsono, Soedarsono (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2018)
The city of Semarang can generally be divided into two regions. The first is the upper region with hilly soil condition, solid and the height almost reaches 350 meters from the sea level.The second is the lower region which is softly grained alluvial plains. The position of the lower land of Semarang has same height with the sea level, so that is too risky when the water overflows onto mainland. The issues that arise, are the soil becomes land subsidence because additional load onto it, consolidation and the excessive groundwater so when tides has come through mainland and flood some territory of the lower land of Semarang. The purpose of this research is to create a map of puddle, because of land subsidence that has made ârobâ (Java Slang) and extensive changes puddle from time to time. That results will make stakeholders to adjust the existing condition. The methodology of research is done by drilling machine on 5 points until 30 meters depth to get soils sample that spreads in the at whole of the lower land of Semarang. The sample has been obtained and also tested by using the mechanical properties and soil properties at UNISSULAâs soil mechanical laboratory. Based on the test lab,it is analyzed to get the result how deep the soil settlement caused due to consolidation. Finally it holds analyzing extensive changes puddle cause of land subsidence by using GIS. The result of this research is puddles map in Semarang city and it changes from time to time. Besides that the analysis is further to the north (seaward) down more, but the time also give the biggest impact of land subsidence.